2007
DOI: 10.1111/j.1365-2885.2007.00864.x
|View full text |Cite
|
Sign up to set email alerts
|

Dirlotapide: a review of its properties and role in the management of obesity in dogs

Abstract: Dirlotapide is a microsomal triglyceride transfer protein (MTP) inhibitor developed specifically for canine weight reduction. MTP catalyzes the assembly of triglyceride-rich apolipoprotein-B containing lipoproteins to form chylomicrons in the intestinal mucosa and very low-density lipoproteins in the liver. Following oral administration, dirlotapide has in vivo selectivity for intestinal MTP compared with hepatic MTP. In addition to reducing intestinal fat absorption, dirlotapide also reduces food intake in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 30 publications
(99 reference statements)
4
31
0
Order By: Relevance
“…In addition, SLx-4090 decreased the body weight gain in ApoE(Ϫ/Ϫ) mice over the course of treatment and had a positive impact on liver and fat stores as evidenced by reductions in fat and liver weight to body weight ratios. The overall reduction in body weight compared with vehicle animals was not the result of a decrease in food intake that has been reported for the MTP inhibitor dirlotapide (Wren et al, 2007). The enterocytic selectivity of SLx-4090 was further supported by the lack of elevation of the liver transaminases even at the highest dose tested.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In addition, SLx-4090 decreased the body weight gain in ApoE(Ϫ/Ϫ) mice over the course of treatment and had a positive impact on liver and fat stores as evidenced by reductions in fat and liver weight to body weight ratios. The overall reduction in body weight compared with vehicle animals was not the result of a decrease in food intake that has been reported for the MTP inhibitor dirlotapide (Wren et al, 2007). The enterocytic selectivity of SLx-4090 was further supported by the lack of elevation of the liver transaminases even at the highest dose tested.…”
Section: Discussionsupporting
confidence: 53%
“…Unfortunately, MTP is also found in a number of additional organs with notably jpet.aspetjournals.org high levels in the liver, retina, and heart (Borén et al, 1998;Li et al, 2005). Inhibition of hepatic MTP decreases the ability of the liver to rid itself of fat, and chronic treatment with first-generation MTP inhibitors resulted in unacceptable rises in liver transaminases and hepatic steatosis in rodent models and humans Lilly and Rader, 2007;Miyazaki et al, 2007;Wren et al, 2007). Inhibition of MTP in the heart and the retina may also elicit adverse effects (Borén et al, 1998;Li et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic inhibition of chylomicron release antagonizes the otherwise strong, eating-inhibitory effect of intraintestinal fat administration under some conditions (139), and this effect may be due to blockade of apolipoprotein AIV formation (139). In contrast, pharmacologic interference with enterocyte TAG synthesis or chylomicron assembly generally inhibits eating (15,170), and some evidence suggests that the eating-inhibitory effect of TAG synthesis blockade may be related to a metabolic shift from TAG synthesis to FAO. In our hands, DGAT1 inhibition failed to reduce food intake when rats were fed regular chow but clearly inhibited eating when rats were fed a high-fat diet, and this effect was accompanied by a metabolic shift from TAG synthesis to FAO (143).…”
Section: Evidence For Fatty Acid Sensing By the Small Intestinementioning
confidence: 91%
“…In addition, recent studies have demonstrated that inhibition of intestinal MTP results in suppression of food intake, accompanied by increased circulating levels of gut peptides such as PYY (Wren et al, 2007). In this study, we examined the effects of JTT-130, an intestine-specific MTP inhibitor, on food intake in Sprague-Dawley rats.…”
Section: Introductionmentioning
confidence: 99%